Analysis Consumer Sustainable Intention of E-Money Using Theory DOI and Theory TPB - Husnil Khatimah; Perengki Susanto (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This research is designed for investigate factors whar make consumers intent to use the e- money for payment transaction at e-marketplaces. Constructs from two theoretical frameworks, i.e. the Diffusion of Innovation Theory (DOI), integrated with Theory of Planned Behavior (TPB) were used to guide the study. Quantitatively 300 samples were distributed to respondents with a cross-sectional survey, but to overcome the bias of the research response, 350 respondents used a cross-sectional study to consumers with the highest level of online purchases in the city of Padang. Relevant hypotheses were formulated and tested using the SEM-PLS technique. The results indicate that all variables significant supported. The findings confirmed that consumer innovation has significant impact toward the intention to use e-money, which this factor is new insight have not proven in several studies. In other hand, the personal norms, perceived behavioral control and attitude is also confirmed the significant effect intent to use e- money. The implications of this study drives for practice and research and future research.